Meningkatkan Keterampilan Membuat Gantungan Kunci Melalui Strategi Joy Learning Pada Siswa Tunagrahita - Ismail, Asella; Arnez, Gaby (Jurnal Penelitian Pendidikan Khusus, 2024)
Thiis reseiarch applies a classiroom aiction resiearch approach to improve motorbike washing skills in class XI students with mild mental retardation at SLB Negeri Muaro Bungo. By adopting the Joy Learning strategy, the reseiarch wias coniducted over tiwo cyicles witih i3 meietings in eacih cyicle, involving 5 students, AZ, JDV, NA, RS and SF, as subjects. Tihe resuilts of the research shiowed a signiificant incirease in the skills of making key chains for the five students, with the final grades of Cycle II respectively reaching AZ students 82%, JDV students 85%, NA students 80%, RS students 83% and SF students 83%, the five categorized as very good. The Joy Learning strategy has proven effective in increasing students' understanding of the steps for making key chains. The learning process was carried out according to plan with good collaboration between students, researchers and teachers, involving planning stages, implementing actions, observing and critical reflection in each cycle. This research makes a positive contribution to the skills of making key chains for students with mild intellectual disabilities